MODEL PAASIAN BERBANTUAN WORDWALL: STRATEGI INOVATIF DALAM MENINGKATKAN KEMANDIRIAN DAN KERJA SAMA SISWA PADA PENDIDIKAN PANCASILA - Nuriyadi; Diani Ayu Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem of this research is the low independence and cooperation among students. When learning, students find it difficult to manage their time and tasks independently, leading them to rely on their peers. They also struggle with collaboration and socialization with other group members. This issue arises because the learning process does not emphasize independent study habits and cooperation. To address this problem, the PAASIAN model (Problem Based Learning, Numbered Heads Together, and SAVI: Somatic, Auditory, Visualization, and Intellectually) and Wordwall media were implemented. The aim of this study is to analyze the improvement in student independence and cooperation. This research employs Classroom Action Research. The results indicate that student independence increased from 25% (less independent) to 100% (very independent) from meetings 1 to 4. Additionally, student cooperation improved from 37.5% (less skilled) to 90% (very skilled) over the same period. Based on these findings, it can be concluded that the PAASIAN learning model and Wordwall media can enhance student independence.